"Fetal Deaths and Sex Ratio Among Progenies of Workers of Operating Rooms in Hospitals of Hamadan " - H Pour-Jafari; DD Farhud (Tehran University of Medical Sciences, 2001)
Workers of operating rooms in hospitals are chronically in exposure to rather higher dose of chemicals, e.g. halothane and nitrous oxide, than general population. Concern that exposure to waste anesthetic gases may cause mutagenic, carcinogenic, or teratogenic changes has provided the impetus for many recent studies. The goal of present work was to determine incidence of the fetal deaths and sex ratio among progenies of workers in operating rooms in hospitals. Results of pregnancies of spouses of all male workers and also pregnancies of female workers of operating rooms in hospitals in Hamadan, Iran, were studied. Total of pregnancies were 200 cases. In a cross-sectional descriptive investigation, the results of all pregnancies of two subject groups were studied for frequencies of fetal deaths (abortions + stillbirths) and sex ratios of progenies and then statistically compared with each other and with general population. The basic primary data were collected by face-to-face interviews and by employing suitable questionnaires. Total of pregnancies of our subject groups were 200 cases (101 cases belong to wives of male workers, and 99 cases belong to the female workers). Frequencies of the fetal deaths in those two groups were 4.96% and 13.13% respectively. Sex ratios of live births were 88.46% and 97.83%. Frequency of fetal deaths in spouse of the male workers were about the same value in general population in Hamadan, but frequency of the fetal deaths in female workers were statistically different from the same value in the general population of Hamadan. Sex ratio of the progenies in both groups (men and women workers) were lower than the same value in the general population in Hamadan. The results of present study showed that it seems probably, work in operating rooms of hospitals would lead to some genetic consequences.